Switching Intentions Among Millennial Banking Customers to Fintech Lending - Muhammad Anif Afandi (International Journal of Islamic Economics and Finance (IJIEF), 2020)
The purpose of this study is to analyze of switching intentions among millennial banking customers to the financing services of FinTech lending in Indonesia using the PPM framework. 245 primary data were collected by Likert 5 scale category which was subsequently conducted data analysis using the OLS method. The results showed that in the perspective of push effects, all factors have no significant effect on switching intentions or in other words the millennial banking customers have considered that credit/financing services in banking is quite good that it does not encourage them to switch. In the perspective of pull effects, ease of use and pricing benefit factors of FinTech lending have significant effect on switching intentions so that it attracts them to switch. Meanwhile, in the perspective of mooring effects, the factors of service products and reputation significantly affect switching intentions so as to impede them to switch. In addition, Islamic banking customers are known to have higher potential to switch to the financing services of FinTech lending. The results of this study provide useful information for the banking industry, FinTech lending and regulators to be able to develop strategies and effective policies amid the potential of customer switching